Analysis of the Questions Item for Biology Olympiad Participants - Subari, Ahmad; Zulyusri, Zulyusri; Violita, Violita (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
Biology Olympiad is one of the national tests run annually. The quality of the item tests needs to be analyzed details. This study aims to determine the quality of the MAN (Public Islamic School) Model Biological Olympiad questions in Jambi City. The subjects in this study were 10 graders of MAN Model Jambi City who attended the Biology Olympiad training. The data analysis technique used in this study was a program called States 4.0.9. The results in the study showed that for the validity of the items at the coefficient level of 5%, there were 13 valid questions and 27 invalid questions. Meanwhile, for the reliability of the questions, the value was 0.46 which was categorized as sufficient. Furthermore, for the difficulty level of the questions, they were 3 questions in the easy category, 16 questions in the medium category, and 21 questions in the difficult category. Then for the results of the distinguishing power of the questions, 7 questions were categorized as very good, 12 questions were categorized as good, 7 questions were categorized as poor, and 14 questions were categorized as very poor. Meanwhile, for the results of the analysis of the quality of distracting items, there were 4 questions with quality was categorized as very good and good, while the rest were classified as poor, poor, and very poor criteria, or those criteria need to be revised.